2019
DOI: 10.1177/0300060519878377
|View full text |Cite
|
Sign up to set email alerts
|

Maternal anxiety, social status, and dental caries formation in children: a cross-sectional study

Abstract: Objective We sought to evaluate the association of maternal anxiety and social status with caries formation in children. Methods Participants comprised 258 pairs of children and their mothers. We collected information regarding age, sex, birth order of children, and mothers’ education and marital status using a questionnaire. The Spielberger Trait Anxiety Inventory was used to determine maternal trait anxiety levels. The children underwent oral examination. Total values for decayed, missing, filled, and total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
(52 reference statements)
0
6
0
Order By: Relevance
“…The findings of the present study were found to be in accordance with the findings of Yıldırım and Aktören [ 32 ], Mummalo et al [ 33 ], Alqutami et al [ 34 ], Weiler et al [ 35 ], and Koga-Ito et al [ 15 ]. Dental caries is a multifactorial disease, and various factors play a role in the formation and progression of dental caries such as biological factors, the presence of cariogenic microorganisms, dietary habits, oral hygiene practices, parental education, and socioeconomic status [ 36 ]. Thus, in this study, these factors were also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the present study were found to be in accordance with the findings of Yıldırım and Aktören [ 32 ], Mummalo et al [ 33 ], Alqutami et al [ 34 ], Weiler et al [ 35 ], and Koga-Ito et al [ 15 ]. Dental caries is a multifactorial disease, and various factors play a role in the formation and progression of dental caries such as biological factors, the presence of cariogenic microorganisms, dietary habits, oral hygiene practices, parental education, and socioeconomic status [ 36 ]. Thus, in this study, these factors were also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Although dental caries has been mitigated by many preventive measures, this disease continues to be a significant threat to oral health, negatively affecting the individual's quality of life. [1][2][3] Nearly half of the world population suffers disability as a consequence of oral health conditions, which remain highly prevalent to this day. 4 According to the Global Burden of Disease 2010, cavitated lesions in permanent teeth were the most prevalent condition among 291 diseases affecting 2.5 billion people worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Furthermore, the parents' psychological status, behavior, and attitudes has been reported to affect their children's general and oral health status. 2 The family and the mother's behaviors affect the child's quality of life, general and oral health, and play a key role in determining the oral health status of children. 2,15,16 The association between the development of dental caries in children and the level of maternal education has been identified.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, primary prevention of ECC has importance because it is easier to prevent the formation of caries than perform treatment that generally needs extensive restorative and surgical treatments of primary teeth, which can be psychologically and financially challenging for children and their families [3,6,7]. Since infants and toddlers are unable to care for themselves and are dependent on their parents, parents, and especially mothers, are primarily responsible for sustaining the oral health of young children as primary caregivers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%